2020
DOI: 10.1590/0366-69132020663802949
|View full text |Cite
|
Sign up to set email alerts
|

Development of nickel and silver ceramic filters supported on K10 montmorillonite clay for water disinfection

Abstract: This study aimed to obtain ceramic filters with bactericidal action for water disinfection. For this, aqueous suspensions of montmorillonite K10 clay were prepared at concentrations of 48%, 50%, and 52%. Later, these were impregnated into polymeric sponges in order to form the ceramic skeletons by using the replica technique. The ceramic filters were submerged in nickel resins doped with 0.25 and 0.50 mol% silver. These resins were obtained by the Pechini method and heat-treated at 600 and 700 ºC for 2 h. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These solids, with their large surface areas, represent an excellent support for the immobilization of metallic nanoparticles [74,170,171]. The resulting hybrid materials can be used in the disinfection process [83,[172][173][174][175]. Chao et al [176] realized a filter paper impregnated with montmorillonite saturated with Fe 3+ cations, which was produced to filter E. coli bacteria present in water.…”
Section: Use Of Montmorillonite-supported Metallic Nanoparticles For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…These solids, with their large surface areas, represent an excellent support for the immobilization of metallic nanoparticles [74,170,171]. The resulting hybrid materials can be used in the disinfection process [83,[172][173][174][175]. Chao et al [176] realized a filter paper impregnated with montmorillonite saturated with Fe 3+ cations, which was produced to filter E. coli bacteria present in water.…”
Section: Use Of Montmorillonite-supported Metallic Nanoparticles For ...mentioning
confidence: 99%
“…The authors confirmed that the result was slightly higher when compared to the use of UV radiation. Jiang et al [174] fabricated a nanomaterial based on montmorillonite decorated with lysozyme-modified silver nanoparticles for bacterial disinfection. The montmorillonite structure prevented the aggregation of the AgNPs and promoted nanomaterial-bacteria interactions.…”
Section: Use Of Montmorillonite-supported Metallic Nanoparticles For ...mentioning
confidence: 99%